Dysphagia in Behçet's syndrome. Issue 2 (March 1971) - Arma, S.; Habibulla, K. S.; Price, J. J.; Collis, J. Leigh
Abstract : The association of dysphagia and Behçet's syndrome is described. Care has been taken to establish the exact cause for the dysphagia, and autonomic nervous system abnormalities were demonstrated. The local condition appears to be similar to but not identical with achalasia. In view of this similarity a Heller's myotomy was performed with a satisfactory result.